2012
DOI: 10.1007/s10943-012-9602-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Spiritual Intelligence Role in Predicting University Students’ Quality of Life

Abstract: The aim of the study is to investigate the spiritual intelligence role in predicting Quchan University students' quality of life. In order to collect data, a sample of 143 students of Quechan University was selected randomly enrolled for 89-90 academic year. The instruments of the data collecting are World Health Organization Quality of Life (WHOQOL) and Spiritual Intelligence Questionnaire. For analyzing the data, the standard deviation, and Pearson's correlation coefficient in descriptive level, and in infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Belief to recover with tawakal (surrender) to God's will can cure the pain and suffering. Prayer and effort can increase self-efficacy [8]. Prayer enhances confidence of cancer patients in addition to seek regular treatment.…”
Section: Spiritual Beliefs and Religiosity Of Cancer Volunteersmentioning
confidence: 99%
“…Belief to recover with tawakal (surrender) to God's will can cure the pain and suffering. Prayer and effort can increase self-efficacy [8]. Prayer enhances confidence of cancer patients in addition to seek regular treatment.…”
Section: Spiritual Beliefs and Religiosity Of Cancer Volunteersmentioning
confidence: 99%
“…The benefits of developing these spheres of human life, as already pointed out by various publications, include increased sense of well-being, optimism, better situational coping, depression and stress reduction. In addition, they bring more meaning to the individual's life, making it more peaceful and comfortable [5][6][7][8][9][10] .…”
Section: Correlation Between Spirituality Religiosity and Quality Ofmentioning
confidence: 99%
“…Spiritual intelligence plays an important role in people's lives and health. Iranian university students questioned about this point and quality of life indicated that there is a positive and relevant relationship between both, that is, the more spiritualized the better the perception of wellbeing 8 . Another study confirmed that there is a positive relationship between quality of life and spiritual well-being in Iranian teenagers 2 .…”
Section: Spirituality and Religiosity In The Quality Of Lifementioning
confidence: 99%
“…(Altay & Avci, 2009) [2] . The role of spiritual intelligence in predicting quality of life among 143 students of Quechan University was investigated by Bolghani-Abadi, Ghofrani and Abde-Khodaei (2012) [9] and concluded that spiritual intelligence significantly predicting the quality of life. Whereas Koohbanani, Dastjerdi, Vahidi and Far (2013) [16] stated that there was no significant relationship between spiritual intelligence and life satisfaction among gifted female high school students.…”
Section: Introductionmentioning
confidence: 99%